Interoceptive posture awareness and accuracy: a novel photographic strategy towards making posture actionable - Weiniger, Steven P.; Schilaty, Nathan D. (Frontiers in Neuroscience, 2024)
Interoception, sometimes referred to as the ‘hidden sense,’ communicates the state of internal conditions for autonomic energy regulation and is important for human motor control as well as self-awareness. The insula, the cortex of interoception, integrates internal senses such as hunger, thirst and emotions. With input from the cerebellum and proprioceptive inputs, it creates a vast sensorimotor network essential for static posture and dynamic movement. With humans being bipedal to allow for improved mobility and energy utilization, greater neuromotor control is required to effectively stabilize and control the four postural zones of mass (i.e., head, torso, pelvis, and lower extremities) over the base of support. In a dynamic state, this neuromotor control that maintains verticality is critical, challenging energy management for somatic motor control as well as visceral and autonomic functions. In this perspective article, the authors promote a simple series of posture photographs to allow one to integrate more accurate alignment of their postural zones of mass with respect to the gravity line by correlating cortical interoception with cognitive feedback. Doing this focuses one on their body perception in space compared to the objective images. Strengthening interoceptive postural awareness can shift the net result of each zone of postural mass during day-to-day movement towards stronger posture biomechanics and can serve as an individualized strategy to optimize function, longevity, and rehabilitation.